Correlation and Path Analysis Studies for Yield Related and Nutritional Traits in Recombinant Inbred Lines of Rice MTU1010 X BR2655 - D. SRINIVASA CHARY, RAMYA RATHOD, L.V. SUBBA RAO, C.N. NEERAJA, K.B. ESWARI and (The Journal of Research, PJTSAU, 2020)
The present study was undertaken to estimate the correlation and path analysis for yield, yield attributing and nutritionaltraits in 190 F8 RILs derived from MTU1010 X BR2655 along with two parents during Rabi-2016-17. Grain yield per plant hadsignificant positive association with panicle length, number of productive tillers per plant, number of filled grains per panicle and1000-grain weight. Path analysis revealed that 1000-grain weight exerted the highest positive direct effect on grain yield followedby plant height, number of filled grains per panicle, days to 50 per cent flowering and number of productive tillers per plantindicating that selection for these characters was likely to bring about an overall improvement in grain yield per plant directly.